Impact of microwave ablation treatment on the biomechanical properties of the distal radius in the dog: A cadaveric study. Issue 7 (24th July 2020) - Kalamaras, Alexandra B.; Wavreille, Vincent; Jones, Stephen C.; Litsky, Alan S.; Selmic, Laura
Abstract: Objective: To determine whether microwave ablation (MWA) modifies the biomechanical properties of the normal distal radius in the dog to better estimate the clinical impact of MWA as a tool for the treatment of neoplastic bone lesions. Study design: Biomechanical experimental study. Sample population: Sixteen pairs of dog forelimbs from 16 canine cadavers. Methods: From each pair of forelimbs, one radius was randomly assigned to an MWA group, and the other radius was randomly assigned to a control group. Bone tunnels were created in each distal radial epiphysis for a length of 6 cm toward the middiaphysis. In the MWA group, the ablation probe was inserted into the bone tunnel for a series of three ablation treatments. Specimens were then tested in three‐point bending to acute failure with the middle point located 3 cm from the distal articular surface (middle of the ablated zone). Load and displacement were continuously recorded to determine maximum displacement and peak load before failure. Data were analyzed with noninferiority tests. Results: The mean peak loads for the control group and MWA group were 1641.9 N and 1590.9 N, respectively. Microwave ablation‐treated radii were not biomechanically inferior to control radii ( P < .0001). Conclusion: Microwave ablation of normal cadaveric dog distal radii did not affect the maximum displacement and peak load before failure. Clinical significance: Microwave ablation does not affect biomechanical bending properties of the distal radius in the dog. Future studies, both cadaveric and in vivo, are required to evaluate the impact of MWA on neoplastic bone.